Impact of Halo and Hormonal Priming on Early Vegetative Growth Phase of Rice Var. MTU 7029 - Mondal, Sananda; Kumar, Mahesh; Bose, Bandana (International Journal of Bio-resource and Stress Management, 2018)
The present piece of work was conducted in the Seed Physiology Laboratory of Institute of Agricultural Sciences, Banaras Hindu University in the year 2011–12, where the rice seeds variety MTU 7029 were primed with different combinations of kinetin (in ppm) and magnesium nitrate (in mM) (2.5 ppm+2 mM, 2.5 ppm+4 mM, 2.5 ppm+6 mM, 2.5 ppm+8 mM, 5 ppm+2 mM, 5 ppm+4 mM, 5 ppm+6 mM, 5 ppm+8 mM kinetin and magnesium nitrate respectively) whereas; seeds without any treatment referred as control (non-primed). Various physio-morphological (shoot and root lengths (in cm), root number, fresh and dry weights (in g)) and biochemical (proline content (mg g-1 dry weight of seedlings), total chlorophyll content (mg g-1) and superoxide dismutase activity (unit×102 g-1 min-1 fresh weight of leaf; at 20 days after sowing)) parameters were studied in the seedlings, obtained from 10, 15 and 20 DAS old primed and non-primed plants. All the primed seeds were found to perform better as compared to non primed control one. However, treatment 2.5 ppm kinetin+4 mM magnesium nitrate performed best among all the treatments and all the studied parameters such as shoot and root lengths, root number, fresh and dry weights, proline content, total chlorophyll content and superoxide dismutase activity in 10, 15 and 20 days after sowing.